Development of a Web-Based Integrated Housing Information System to Support Decision-Making at Ministry of Public Works and Housing (PUPR) Lhokseumawe - Zalfie Ardian; Zarira Reri Najiha; Rahma Fitria; Rizky Putra Fhonna; Athiyatul Ulya (Sisfo: Jurnal Ilmiah Sistem Informasi, 2026)
The management of housing data that is not integrated often leads to delays in information, data inconsistency, and inefficiency in decision-making processes within government institutions. The Public Works and Housing Agency (PUPR) of Lhokseumawe City faces similar issues, where housing data management is still conducted manually using spreadsheet-based systems. This research aims to develop a web-based integrated housing information system to improve efficiency, accuracy, and accessibility of housing data. The methodology includes user requirement analysis, system design using Unified Modeling Language (UML), and system implementation using PHP and MySQL. The system provides features such as authentication, data management, and visualization dashboards. The results show that the system improves data processing efficiency, reduces redundancy, and supports decision-making in housing rehabilitation programs.